2016
DOI: 10.3389/fpubh.2016.00281
|View full text |Cite
|
Sign up to set email alerts
|

10 Years of Environmental Change on the Slopes of Mount Kilimanjaro and Its Associated Shift in Malaria Vector Distributions

Abstract: IntroductionMalaria prevalence has declined in the Kilimanjaro region of Tanzania over the past 10 years, particularly at lower altitudes. While this decline has been related to the scale-up of long-lasting insecticidal nets to achieve universal coverage targets, it has also been attributed to changes in environmental factors that are important for enabling and sustaining malaria transmission.ObjectivesHerein, we apply spatial analytical approaches to investigate the impact of environmental and demographic cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 47 publications
(61 reference statements)
0
19
0
Order By: Relevance
“…With increasing quality and availability of remote sensing data, it might be possible to predict altitudinal movement of key vector species such as An. arabiensis [ 62 ]. There will remain uncertainty about local-scale altitudinal shifts in temperature and rainfall and their resulting impact on malaria risks.…”
Section: Knowledge Gaps and The Questions They Posementioning
confidence: 99%
“…With increasing quality and availability of remote sensing data, it might be possible to predict altitudinal movement of key vector species such as An. arabiensis [ 62 ]. There will remain uncertainty about local-scale altitudinal shifts in temperature and rainfall and their resulting impact on malaria risks.…”
Section: Knowledge Gaps and The Questions They Posementioning
confidence: 99%
“…In the U.S., species such as Culex coronator (Dyar and Knab) and Culex erraticus (Dyar and Knab) in Central America and the southern U.S. have been documented in northern latitudes outside of these species' historical distributions 22,23 . Other studies have shown changes in mosquito species distributions linked with temperature changes along altitudinal gradients 24,25 (though these changes in altitudinal gradients could also be driven by changes in land use) and projected range expansions under various climate change scenarios 21 . Overall, identifying species expansions strictly due to warming temperatures is difficult to assess as changes in climate are often coupled with factors such as land use changes and human behavior that feedback into climate change.…”
mentioning
confidence: 99%
“…Evidence is nonetheless emerging that a mixture of anthropogenic activities related to land cover change, combined with increased temperatures, is shifting the species range in specific areas (e.g. Fuller et al, 2012;Kulkarni et al, 2016) and may either cause local extinction (Escobar et al, 2016), or an overall increase in environmental suitability combined with seasonal and range shifts (e.g. Ryan et al, 2015).…”
Section: Anophelesmentioning
confidence: 99%